2011
DOI: 10.1128/aem.00015-11
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Methicillin-Resistant Staphylococcus aureus Strains in Marine and Freshwater Samples by the Most-Probable-Number Method

Abstract: Recreational beach environments have been recently identified as a potential reservoir for methicillinresistant Staphylococcus aureus (MRSA); however, accurate quantification methods are needed for the development of risk assessments. This novel most-probable-number approach for MRSA quantification offers improved sensitivity and specificity by combining broth enrichment with MRSA-specific chromogenic agar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…after 7 days. Sampling events on August 2 (marine water n = 4; freshwater n = 21) and August 30 (marine water n = 4; freshwater n = 18; dry sand n = 4; wet sand n = 4) for beach A and July 22 (marine water n = 3; freshwater n = 9; wet sand n = 4; dry sand n = 3) freshwater and for August 16 (marine water n = 3; freshwater n = 8; wet sand n = 4; dry sand n = 3) for beach B were quantified using the most‐probable number (MPN) technique as previously described (Levin‐Edens et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…after 7 days. Sampling events on August 2 (marine water n = 4; freshwater n = 21) and August 30 (marine water n = 4; freshwater n = 18; dry sand n = 4; wet sand n = 4) for beach A and July 22 (marine water n = 3; freshwater n = 9; wet sand n = 4; dry sand n = 3) freshwater and for August 16 (marine water n = 3; freshwater n = 8; wet sand n = 4; dry sand n = 3) for beach B were quantified using the most‐probable number (MPN) technique as previously described (Levin‐Edens et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…β‐Hemolytic, coagulase‐positive S. aureus that grew on Bacto ® Staphylococcus Medium 110 supplemented with methicillin were considered presumptive MRSA, and the presence of the mecA gene was determined by PCR (see next section). For the sampling events that were quantitatively processed, presumptive MRSA isolates were isolated as previously described (Levin‐Edens et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…Also, Soge et al ( 47 ) described the isolation and characterization of methicillin-resistant Staphylococcus aureus from marine water and intertidal samples from Pacific Northwest marine beaches. Levin-Edens et al ( 28 ) showed that sewer overflows during storm events and urban runoff from high density residential areas may contribute to the contamination of the marine environment with methicillin-resistant Staphylococcus aureus .…”
Section: Resultsmentioning
confidence: 99%
“…This means that S. aureus possesses resistance against an array of antibiotic classes, which is referred to as multidrug-resistant S. aureus (MDRSA). In humans and animals, MDRSA infections are acquired through inhalation [7], direct contact with infected objects, persons, or animals, and consumption of contaminated animals products [8] or water [9].…”
Section: Introductionmentioning
confidence: 99%